KEBIJAKAN FISKAL DAN IMPLIKASINYA TERHADAP PEMBANGUNAN EKONOMI: Kajian Konseptual & Teoritis Dalam Perspektif Ekonomi Islam - Ahmad Mansur (El-Qist: Journal of Islamic Economics and Business (JIEB), 2012)
Fiscal policy beside monetary policy is usually used by the government to overcome the macro economic problems regarding stabilization in the short-run such as control of inflation to make it low inflation, alleviating poverty, achieving full employment and control of balance of payment to make it in balance or even surplus and in the long-run achieving economic growth, prosperity and sustainable economic development. This research tries to investigate the role of fiscal policy and its implication on economic development in an Islamic perspective conceptually and theoretically. It found that the instrument of fiscal policy in an Islamic perspective not only using tax and government expenditure but also zakah which could be utilized to counter cyclical fiscal policy. Zakah as one of the instrument of fiscal policy could also be utilized to achieve equitable distribution of income and wealth as the basic characteristic of zakah is redistribution of wealth taken from the rich and given to the poor ones. In the time of stagflation, zakah instrument could become powerful tool to overcome that problem through demand side and thus stimulate production. Although this mechanism is not as simple as we perceived, zakah does help overcome the macroeconomic problems on conditions that we also adopt and implement Islamic values and Islamic norms in our economy.